Scientific communication or a qualification for an academic career? What use is publishing papers in psychology journals? - Osca-Lluch, Julia; González-Sala, Francisco; Haba-Osca, Julia; Tortosa, Francisco; Peñaranda-Ortega, Maria (Anales de Psicología / Annals of Psychology, 2018)
This paper analyses all psychology journals included in the different categories of the JCR (SCI and SSCI) and SJR databases during the period 2014-2016 in order to identify the journals that are better positioned in the discipline, and the specialities and countries with the highest number of publications indexed in such databases. Method: The distribution of psychology journals by country, quartile, and subject category was studied in order to determine the total number and position of journals in each country, and to identify the countries with more journals of ‘excellence’ in psychology in the international scene. Results: The United States and the United Kingdom had the highest number of journals included in the databases, as well as the Netherlands, Germany, France and Spain. Only 11 countries have psychology journals in quartile 1 in JCR, and 14 in SJR databases. Conclusions: As a result of the application of new evaluation criteria in psychology research in Spain, the paper addresses the difficulties and consequences that some of these measures may have for the survival of psychology journals that do not have a position in quartile 1 or 2 in the databases used for the evaluation of professionals’ research in this discipline